2016
DOI: 10.1080/24699322.2016.1240303
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence classification methods of atrial fibrillation with implementation technology

Abstract: Background: Atrial fibrillation (AFIB) is one of the most common types of arrhythmia, which leads to heart failure and stroke to public. As AFIB has the high potential to cause permanent disability in patients, its early detection is extremely important. There are different types of AFIB classification algorithm that have been proposed by researchers in recent years. Methods: This paper reviews the features of AFIB in terms of ECG morphological features and heart rate variability (HRV) analysis on different me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The pulse-like signals shown in the lower section of each figure are the trigger signals to activate the VADs as opening commands. Though there are different disturbances in the original ECG signals as shown in the upper section of each figure, such as low frequency drift, amplitude inconsistency, disorder period, atrial fibrillation, which is one of the most common types of arrhythmia[27], the proposed method can always accurately and stably identify the interest signals, These simulation results based on the ECG signals from authoritative database confirmed that this method including the key algorithm and the program based on it is of high adaptability.…”
mentioning
confidence: 67%
“…The pulse-like signals shown in the lower section of each figure are the trigger signals to activate the VADs as opening commands. Though there are different disturbances in the original ECG signals as shown in the upper section of each figure, such as low frequency drift, amplitude inconsistency, disorder period, atrial fibrillation, which is one of the most common types of arrhythmia[27], the proposed method can always accurately and stably identify the interest signals, These simulation results based on the ECG signals from authoritative database confirmed that this method including the key algorithm and the program based on it is of high adaptability.…”
mentioning
confidence: 67%
“…Additionally, commonly known classes include statistical or distribution function features. For the features extraction study with conventional domains please consult [84]. But here in this study, classification of feature extraction is driven by the source activities that generate the data or features.…”
Section: Features Extractionmentioning
confidence: 99%
“…RR Interval is the most popular feature for the detection of AF and many other types of arrhythmia. Some commonly used RR interval based time, frequency, spectral and distribution domain features are listed in Table VI [19], [84], [100]- [102].…”
Section: Features Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI is an English standard for intelligence. Theories, systems, technologies, and systems used in research and simulation are new science; human wisdom is constantly expanding [22,23]. The roles of AI technology in visual media communication design are the following:…”
Section: Ai Technologymentioning
confidence: 99%